UJI FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN EKSTRAK METANOL JARINGAN BUAH TANAMAN BINTARO (Cerbera manghas) - Meysi Yulianti; Usman Usman (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Bintaro plant (Cerbera manghas) is a plant that contains toxin, especially in the fruit which contains the toxic compound cerberin. However, even though it contains poison, the fruit of the bintaro plant also has the potential as an antioxidant. The purpose of this study was to determine the secondary metabolite compounds and antioxidant activity of the methanol extract of the fruit of the bintaro plant. Phytochemical test analysis was carried out by means of a color test, including the test for alkaloids, flavonoids, phenolics, steroids, triterpenoids, saponins and tannins. As for the antioxidant activity test using the DPPH method by measuring the absorption at a wavelength of 517 nm. The results of the phytochemical test showed that the methanol extract of the fruit of the Bintaro plant contained alkaloid, phenolic and triterpenoid compounds. Then the results of the antioxidant activity test of the methanol extract of the fruit of the Bintaro plant has an IC50 value of 87,013 ± 0.022 ppm. Based on the IC50 value, it can be concluded that the methanol extract of the fruit of the Bintaro plant has antioxidant activity with a strong category. Keywords: Antioxidant, bintaro fruit, phytochemical test